The progesterone receptor gene maps to human chromosome band 11q13, the site of the mammary oncogene int-2. - Law, M L (1987)
Progesterone is involved in the development and progression of breast cancers, and progesterone receptors (PR) are important markers of hormone dependence and disease prognosis. We have used a human PR cDNA probe, genomic DNA blotting of a series of Chinese hamster-human cell hybrids, and in situ hybridization to map the human PR gene to chromosome 11, band q13. This band also contains the human homolog of the mouse mammary tumor virus integration site, int-2, which surrounds a protooncogene thought to be involved in the development of murine mammary cancers. That these two genes share the same chromosomal location raises important questions about their possible linkage and about the relationship between the mammary-specific oncogene and the steroid hormone in the development, growth, and hormone dependence of human breast cancers.